MORALITAS PAJAK MEMODERASI SELF ASSESSMENT SYSTEM DAN MONEY ETHICS TERHADAP TINDAKAN TAX EVASION PADA KANTOR PELAYANAN PAJAK PRATAMA MAKASSAR SELATAN - Ramdani, Muh. Reza; Lestari, Ismi Ayu (Pusat Penerbitan dan Publikasi Ilmiah FEB-UMI, 2023)
This research aims to test Tax Morality Moderating the Self Assessment System and Money Ethics Against Tax Evasion Actions at KPP Pratama South Makassar. Population in this study were individual taxpayers registered at KPP Pratama South Makassar, namely 159,626 individual taxpayers, while the sample in this study was determined using the Slovin formula so that the total sample in this study was 100 taxpayers. This research uses field research methods. The statistical method used to test the hypothesis uses the partial least squares application. Results of the analysis show that the Self Assessment System and Money Ethics simultaneously have a positive and significant effect on tax evasion, while morality as a moderator weakens the influence of the Self Assessment System and Money Ethics on tax evasion.